2015
DOI: 10.1371/journal.ppat.1005162
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria meningitidis Type IV Pili Composed of Sequence Invariable Pilins Are Masked by Multisite Glycosylation

Abstract: The ability of pathogens to cause disease depends on their aptitude to escape the immune system. Type IV pili are extracellular filamentous virulence factors composed of pilin monomers and frequently expressed by bacterial pathogens. As such they are major targets for the host immune system. In the human pathogen Neisseria meningitidis, strains expressing class I pilins contain a genetic recombination system that promotes variation of the pilin sequence and is thought to aid immune escape. However, numerous hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 59 publications
1
76
0
Order By: Relevance
“…Because opsonization is mediated by the binding of host immune proteins (commonly antibodies), the latter studies support the notion that the purpose of C-terminal glycosylation could be to interfere with immune recognition in vivo. Similarly, Gault et al (25) recently showed that hypervirulent N. meningitidis strains with class II pilins are more heavily glycosylated than their class I counterparts.…”
Section: Journal Of Biological Chemistry 22929mentioning
confidence: 90%
See 3 more Smart Citations
“…Because opsonization is mediated by the binding of host immune proteins (commonly antibodies), the latter studies support the notion that the purpose of C-terminal glycosylation could be to interfere with immune recognition in vivo. Similarly, Gault et al (25) recently showed that hypervirulent N. meningitidis strains with class II pilins are more heavily glycosylated than their class I counterparts.…”
Section: Journal Of Biological Chemistry 22929mentioning
confidence: 90%
“…If C-terminal glycosylation in Acinetobacter type IV pili reduces recognition by host immune proteins, one might expect that the pilins from strains lacking a C-terminal glycan would face greater pressure to diversify as has been shown in N. meningitidis (25). Using our alignment of 49 PilA sequences, we separated protein sequences into tfpOϪ and tfpOϩ groups and compared the variability of their surface-exposed residues.…”
Section: Journal Of Biological Chemistry 22929mentioning
confidence: 99%
See 2 more Smart Citations
“…Top-down proteomics (15), which implies the analysis of complex protein samples without prior enzymatic digestion, emerged recently as a powerful method for unambiguous characterization of intact proteoforms (16) bearing multiple PTMs in various combinations (17,18). With the capabilities of the latest high-resolution tandem mass spectrometry systems, it is now possible to envision an ambitious goal: perform high-throughput discovery of proteoforms on a proteomewide scale (19), analyzing both qualitative (20) and quantitative (21,22) changes at the proteoform level.…”
mentioning
confidence: 99%